Filsafat Pendidikan Demokrasi sebagai Landasan Pendidikan Masyarakat Indonesia Baru - Fattah Hanurawan (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Democratic Philosophy of Education as Education Foundation for the New Indonesian Society. Philosophy of education is a study of general theoretical foundations of the nature, aims, and methods of education. As a multi-religion and a multicultural society, Indonesia should develop a democratic philosophy of education. A strategy to develop such a philosophy of education can be based on a synthesis combining global-progressive education and Indonesian local-modern style values. While the former emphasizes education as an instrument for social reform to achieve a democratic society, the latter can be based on religions, faiths, cultural beliefs, and state-ideology-based values.